Tinjauan Teologi Kontekstual terhadap Budaya SIJAGARON (Simbol dalam Upacara Kematian Adat Batak Toba) (International Forum of Researchers and Lecturers, 2025)
The Toba Batak culture has a strong symbolic richness, especially in the traditional rituals of death which are full of theological and social meanings. One of the important symbols in the ceremony is Sijagaron, which literally means